A Bayesian Framework to Assess the Usability of Dry Powder Inhalers in a Cohort of Asthma Adolescents in Italy - Roberto Walter Dal Negro; Massimiliano Povero (MDPI AG, 2021)
The useability of DPIs (dry powder inhalers) depends on several factors that are influenced by the patients' subjectivity and objectivity. The short-form global usability score (S-GUS), a specific tool for the quick ranking and comparison in real life of an inhaler's usability, was used to investigate six of the most prescribed DPIs (Breezhaler, Diskus, Ellipta, Nexthaler, Spiromax, and Turbohaler) in consecutive asthma patients aged <18 years. A Bayesian indirect comparison (IC) was carried out to merge all pairwise comparisons between the six DPIs. Thirty-three subjects participated: eighteen tested Breezhaler, Spiromax, Nexthaler, and Ellipta simultaneously, while fifteen tested Breezhaler, Spiromax, Diskus, and Turbohaler. The estimates of the S-GUS, by the IC model, allowed us to rank the DPIs by their degree of usability: Ellipta, Diskus, and Spiromax were classified as "good to pretty good" (S-GUS > 15), while Spiromax, Turbohaler, and Breezhaler were classified as "insufficient" (S-GUS < 15). The multidomain assessment is recommended in asthma adolescents in order to approximate the effective usability of different DPIs as best as possible. The S-GUS proves particularly suitable in current clinical practice because of the short time required for its use in adolescents.